The best man in Texas - Ferrarella, Marie (Ferrarella, Marie. Forever, Texas., 2021)
"Jason Eastwood was thrilled to be his cousin's best man- even better, it came with a job offer! But he didn't expect Adelyn Montenegro, the maid of honor, to end up involved in both. They may have hit it off at the wedding, yet neither of them is looking for love, not when they have careers and lives to establish. Still, as they work together to build the hospital that's meaningful to them both, the pull between them becomes hard to resist. But will they be able to put their preconceived ideas about relationships aside, or will she let the best man slip away?"--Amazon